[Rezension von: Middleton, Paul, The violence of the lamb : martyrs as agents of divine judgement in the Book of Revelation] - Decock, Paul Bernard (Neotestamentica, 2020)
Paul Middleton has been studying martyrdom in early Christianity for many years. In this work, he applies his expertise in a stimulating way to the Book of Revelation. Against those who would see the image of “the Lamb that was slain” as a “correction” of the Messiah as a Lion, Middleton shows that both have their importance: “Significantly, it is his crucifixion that is the reason for Jesus’ exalted status” (99). Christ is the proto-martyr, the model for all followers of Christ. The martyr’s death is the way to life, to exaltation and power. Acts 14:22, which is referred to in a footnote (219 n. 127), expresses this well: “through many tribulations we must enter the kingdom of God” (διὰ πολλῶν θλίψεων δεῖ ἡμᾶς εἰσελθεῖν εἰς τὴν βασιλείαν τοῦ θεοῦ). Middleton’s study is a challenge, like an antithesis, to the views of those who want to see the Apocalypse as a call to non-violence. In response to this way of reading the Apocalypse, he focuses on the violent judgment by which God’s rule is established. The martyrs are not only the beneficiaries of this violent judgment, but they even have the privilege of taking part in it under the leadership of the Lamb, of the conquering Lion of the tribe of Judah (Rev 5:5). “In consequence, John encouraged all his readers to seek martyrdom” (1).